Integrated geophysical investigations in Hierapolis of Phrygia (Turkey). Issue 1 (1st September 2012) - Scardozzi, Giuseppe; Giese, Stefan; Hübner, Christian
Abstract : This paper concerns the various methods of geophysical prospecting (ground‐penetrating radar, magnetometry and electrical resistivity tomography) applied in Hierapolis of Phrygia, by the Italian Archaeological Mission, during the campaigns of 2007 and 2008. In one case, GPR measurements were verified through excavations during the campaign of 2010, which clarified the causes of different anomalies. The integration between the different methods (in turn integrated with other exploration methods of the surface, such as archaeological surveys and remote sensing from an aerial platform and satellite), applied in areas of the city with different geological characteristics, allowed the retrieval of important data on the urban layout in areas characterized by thick colluvial and alluvial deposits and in areas where there are extensive limestone formations that have formed recently (after an earthquake in the middle of the 7 th century AD) and have been incorporated into the ancient remains.